1989
DOI: 10.1104/pp.90.4.1422
|View full text |Cite
|
Sign up to set email alerts
|

Separation and Characterization of Inositol Phospholipids from the Pulvini of Samanea saman

Abstract: To supplement current thin-layer chromatographic methods for separation and quantitation of plant phospholipids, an altemative method, high-performance liquid chromatography was developed. The major inositol-containing lipids from the pulvini of Samanea saman Merr. were identified as phosphatidylinositol, phosphatidylinositol phosphate, and phosphafidylinositol bisphosphate based on comigration with authentic standards on high-performance liquid chromatography and on thin-layer chromatography. The patterns of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
17
0

Year Published

1989
1989
2003
2003

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 36 publications
(19 citation statements)
references
References 26 publications
2
17
0
Order By: Relevance
“…inositol was incorporated into PtdInsP but the level was very low, limiting our ability to detect its incorporation into PtdInsP 2. Much of the problem lay in the poor uptake together with metabolism of that which was taken up, and judging from our own observations (data not shown) and previous reports, this is typical of plant cells (Cot~ et al 1987;Drebak et al 1988;Cot6 et al 1989;Rinc6n et al 1989;Rinc6n and Boss 1990). The 32p-labelling kinetics of PtdInsP and PtdlnsP 2 during incorporation and pulse-chase experiments were obviously different from those of the structural lipids and were characteristic of lipids expressing a high turnover rate.…”
Section: Discussionsupporting
confidence: 62%
See 2 more Smart Citations
“…inositol was incorporated into PtdInsP but the level was very low, limiting our ability to detect its incorporation into PtdInsP 2. Much of the problem lay in the poor uptake together with metabolism of that which was taken up, and judging from our own observations (data not shown) and previous reports, this is typical of plant cells (Cot~ et al 1987;Drebak et al 1988;Cot6 et al 1989;Rinc6n et al 1989;Rinc6n and Boss 1990). The 32p-labelling kinetics of PtdInsP and PtdlnsP 2 during incorporation and pulse-chase experiments were obviously different from those of the structural lipids and were characteristic of lipids expressing a high turnover rate.…”
Section: Discussionsupporting
confidence: 62%
“…Analysis of PtdInsP in carnation petals showed the presence of both PtdIns(3)P and PtdIns(4)P. Since PtdIns(3)P has also been found in Chlamydomonas (Irvine et al 1992) and in the aquatic monocotylodon Spirodella polyrhiza (Brearley and Hanke 1992) its presence in carnation suggests that this signalling system, which is still being elucidated for animal cells (Downes and Carter 1991;Irvine 1992;Panayotou and Waterfield 1992), is also common in plants. The low level of PtdInsP 2 in carnation petals prevented us from analyzing this lipid for the presence of 3-isomers, but since the most prevalent isomer PtdIns(3,4)P 2 constitutes less than 1% of the PtdInsP 2 pool in animal and lower-plant cells (Downes and Carter 1991 ;Irvine et al 1992), we presume that the PtdInsP2 found in carnation is predominantly PtdIns(4,5)P2, as has been demonstrated earlier for other plants (Cot6 et al 1989;Irvine et al 1989).…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…The mechanism of IAA action might involve second messenger molecules derived from PI phosphate hydrolysis, such as diacylglycerol and IP3 and/or Ca2" ions. The presence of IP3 in plant tissues has been confirmed (4,6,12) and it has been shown that IP3 is able to promote calcium release from intracellular sources in plants, as well (8,21,22).…”
Section: Resultsmentioning
confidence: 85%
“…Inositol phospholipids (2,4,13,21) and inositol phosphates (3) have been identified in plant tissues. Furthermore, IP3-stimulated release of calcium from plant microsomal vesicles (7) and from plant vacuolar vesicles (18) has been demonstrated.…”
mentioning
confidence: 99%